Mock meat in the butchery: Nudging consumers toward meat substitutes - Vandenbroele, Jolien; Slabbinck, Hendrik; Van Kerckhove, Anneleen; Vermeir, Iris (Organizational behavior and human decision processes, 2021)
•A field experiment optimizes the choice architecture for meat substitutes.•The choice architecture increases only meat substitute sales significantly, not meat.•Pairwise presentation and product visibility positively affect this shift.•Results are benchmarked against a pre-intervention period and eight control stores. Is it possible to nudge consumers to swap their chicken sandwich for a meat substitute? A field study tests whether adapting the choice architecture of a large retail store increases the purchase of meat substitutes among nonusers. Instead of offering meat substitutes exclusively in a separate, vegetarian section, this study places them next to similar meat products in the butchery. As such, we (1) increase the meat substitutes’ visibility and (2) offer them in pairs with their meat-based counterparts. Doing so enhances sales of meat substitutes, relative to both past sales in the experimental store and sales in eight other control stores that serve as benchmarks. No backfire effect was observed as meat product sales did not increase significantly. A follow-up study disentangles the effect of product visibility and pairwise presentation. Both product visibility and pairwise presentation increase sales of meat substitutes. However, when visibility is high, fewer meat substitutes were sold in a pairwise presentation.